A new monoterpenoid glycoside and a new phenolic glycoside isolated from Dracocephalum moldavica and their anti-complementary activity. Issue 2 (17th January 2023) - Wang, Jiaming; Sun, Jinfeng; Jin, Long; Wang, Mengjie; Huang, Yanyan; Jin, Mei; Zhou, Wei; Li, Gao
Abstract: A new monoterpenoid glycoside (1 R, 2 R, 4 S )-1, 8-epoxy- p -menthan-2- O - β -D-glucopyranosyl-(1→4)- β -D-glucopyranoside (1 ) and a new phenolic glycoside, cis -1-(3-hydroxy-4-methoxyphenyl)-2-butene-4- O - α -L-rhamnopyranosyl-(1→3)- O - β -D-glucopyranoside (2 ) were isolated from the dried aerial parts of Dracocephalum moldavica, together with 12 known compounds. Compound 5 was isolated from the Lamiaceae family for the first time, compounds 3, 4, 6 and 8 –12 were identified from the genus Dracocephalum for the first time and compounds 7 and 13 –14 were reported from the D. moldavica for the first time. All the compounds were evaluated for anti-complementary activity against the classical and alternative pathways. Compounds 2 –4, 8 and 11 showed anti-complementary activity to different extents, with CH50 and AP50 values ranging from 0.78–1.24 and 1.52–1.84 mM, respectively. The targets of compounds 2 –4, 8 and 11 in complement activation cascade were identified as well. Graphical Abstract: UF0001